1997
DOI: 10.1177/0146167297234002
|View full text |Cite
|
Sign up to set email alerts
|

The Language of Love: The Difference a Preposition Makes

Abstract: The terms love and in love are often used in common discourse. A social categorical approach, whereby the actual members of an individual's social categories are examined, was used to investigate the differential meaning of these terms. It was hypothesized that (a) the membership of the love category would be larger than that of the in love category; (b) the membership of the in love category would be encapsulated within the love category membership, indicating that love is the higher order generic term; (c) t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
2

Year Published

1999
1999
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 26 publications
1
18
0
2
Order By: Relevance
“…Sternberg (1986) defined passion in terms of drives leading to "romance, physical attraction, sexual consummation, and the like in loving relationships" (p. 120). Meyers and Berscheid (1997) cautioned that sexual attraction and desire are not synonymous with romantic love and are not sufficient conditions for experiencing romantic love, with which we agree, for indeed sexual desire in particular may be felt in relatively anonymous contexts (even toward movie characters) where there is no question of love. Still, Meyers and Berscheid found that people were reluctant to label their feelings in a romantic relationship as being "love" unless they felt sexual attraction toward the person.…”
Section: Existing Concepts Of Passionmentioning
confidence: 80%
“…Sternberg (1986) defined passion in terms of drives leading to "romance, physical attraction, sexual consummation, and the like in loving relationships" (p. 120). Meyers and Berscheid (1997) cautioned that sexual attraction and desire are not synonymous with romantic love and are not sufficient conditions for experiencing romantic love, with which we agree, for indeed sexual desire in particular may be felt in relatively anonymous contexts (even toward movie characters) where there is no question of love. Still, Meyers and Berscheid found that people were reluctant to label their feelings in a romantic relationship as being "love" unless they felt sexual attraction toward the person.…”
Section: Existing Concepts Of Passionmentioning
confidence: 80%
“…Overall, however, they seem to agree that all of the brain systems for passionate love, sexual desire, and attachment do in fact communicate and coordinate with one another or, in other words, conclude that love and lust are tightly related but not identical (see Meyers & Berscheid, 1997;Berscheid and Hatfield, 1969). Our question is more as to when love and lust produce different psychological effects.…”
Section: Limitations To Our Studiesmentioning
confidence: 99%
“…There is some research suggesting this is the case, most notably the finding by Meyers and Berscheid (1997) that females are mentioned more as recipients of love than are males. Research has also shown that women are more likely to receive help than men (Eagly and Crowley 1986).…”
Section: Gender Differences In Responsivenessmentioning
confidence: 99%